2015
DOI: 10.1242/dmm.017889
|View full text |Cite
|
Sign up to set email alerts
|

Acute upregulation of hedgehog signaling in mice causes differential effects on cranial morphology

Abstract: Hedgehog (HH) signaling, and particularly signaling by sonic hedgehog (SHH), is implicated in several essential activities during morphogenesis, and its misexpression causes a number of developmental disorders in humans. In particular, a reduced mitogenic response of cerebellar granule cell precursors to SHH signaling in a mouse model for Down syndrome (DS), Ts65Dn, is substantially responsible for reduced cerebellar size. A single treatment of newborn trisomic mice with an agonist of the SHH pathway (SAG) nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Eu; Ptch +/− mice also have slightly raised and rounded cranial vaults compared with the “flatter” vaults of Eu;WT mice, suggesting that, while subtle, the cranial changes caused by the absence of one Ptch allele are similar in both the Eu; Ptch +/− and Ts; Ptch +/− . Given that substantial perturbations in SHH signaling can cause serious craniofacial defects (Hu and Helms, ; Hu et al, ; Tapadia et al, ; Cordero et al, ; Singh et al, ), our results are surprising in that we did not find overt changes in the facial morphology of the Eu; Ptch1 +/− mice compared with Eu;WT.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Eu; Ptch +/− mice also have slightly raised and rounded cranial vaults compared with the “flatter” vaults of Eu;WT mice, suggesting that, while subtle, the cranial changes caused by the absence of one Ptch allele are similar in both the Eu; Ptch +/− and Ts; Ptch +/− . Given that substantial perturbations in SHH signaling can cause serious craniofacial defects (Hu and Helms, ; Hu et al, ; Tapadia et al, ; Cordero et al, ; Singh et al, ), our results are surprising in that we did not find overt changes in the facial morphology of the Eu; Ptch1 +/− mice compared with Eu;WT.…”
Section: Discussionmentioning
confidence: 48%
“…The subset of nine SAG treated euploid mice (orange dots on the positive end of PC1) shared a snout morphology distinct from all the other mice. These nine animals had retracted and depressed nasal bones, medio‐laterally expanded snouts and prominent ridging along the lateral aspects of the fronto‐nasal‐premaxillary junction (Singh et al, ); none of the Ptch +/− mice (euploid or trisomic) showed shape deformations similar to the changes exhibited by the affected SAG‐treated mice. PC2 (18.9%) separated all the trisomic mice, regardless of genotype, from all the euploid mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, experimental models for domestication can provide ways to test the role of NCC and other developmental pathways in generating traits most commonly found in domesticated animals. For example, perturbations in the sonic hedgehog pathway [3943], fibroblast growth factors and their respective receptors [4446] and bone morphogenetic proteins [4749] affect growth and development of the craniofacial form, but the role of NCC in regulating these important developmental networks still needs further investigation [50]. …”
Section: Resultsmentioning
confidence: 99%